Synthesis of Bioactive Three-dimensional Silicon-oxide Nanofibrous Structures on the Silicon Substrate for Bionic Devices’ Fabrication - Candace Colpitts; Amirkianoosh Kiani (Nanomaterials and Nanotechnology)
Bionic devices are implants that replace biological functions that have been lost due to damaged or lost tissue. The challenge of this area is to find the appropriate materials to match the biocompatible criteria with the same mechanical and electrical performance. In this research, a new method is introduced for the enhance‐ ment of silicon biocompatibility by fabrication of a 3D nanofibrous layer on the silicon surface, induced by nanosecond laser pulses at a high repetition rate and power. It was found that the laser treatment with small‐ er line spacing and a higher overlap number enhanced the biocompatibility of silicon. The results display a promis‐ ing improvement in the biocompatibility of silicon for the production of biomedical devices such as sensors, bio- MEMS and nano-biomaterial fabrications.